Host microenvironment in breast cancer development: Inflammatory cells, cytokines and chemokines in breast cancer progression: reciprocal tumor–microenvironment interactions - Ben-Baruch, A (BioMed Central, 2003)
A comprehensive overview of breast cancer development and progression suggests that the process is influenced by intrinsic properties of the tumor cells, as well as by microenvironmental factors. Indeed, in breast carcinoma, an intensive interplay exists between the tumor cells on one hand, and inflammatory cells/cytokines/chemokines on the other. The purpose of the present review is to outline the reciprocal interactions that exist between these different elements, and to shed light on their potential involvement in breast cancer development and progression.